INTELIGENCIA ARTIFICIAL Y LA PERSONALIZACIÓN DE APRENDIZAJES DE LOS ESTUDIANTES DE BACHILLERATO EN INFORMÁTICA DE LA UNIDAD EDUCATIVA TEODORO ALVARADO GARAICOA PERIODO ACADÉMICO OCTUBRE 2023 – MARZO 2024. - CRESPO VILLAMAR LEONELA GISSELA (2024)
The present document makes a study on the significant contribution that artificial intelligence (AI) has in the personalization of learning. Its analysis allows us to recognize that these tools are an integral part of the new digital era, information and technological innovation, globalized contexts in which young people currently operate. The research highlights the opportunity to leverage these technologies to boost learning efficiency. The main objective of the research is to determine how the contribution of Artificial Intelligence in the personalization of learning of high school students in computer science at the Teodoro Alvarado Garaicoa Educational Unit academic period October 2023 - March 2024. The methodology used in the research It has a mixed approach, the research is descriptive and also bibliographic. The survey technique is used as a data collection tool, aimed at a representative sample of 126 students. The results obtained from these surveys will be presented through statistical tables and graphs, providing a visual and quantitative representation of the research findings. The results after the analysis allow us to propose that high school computer science teachers include applications with artificial intelligence such as Google Bat, Gamma and ChatGPT, which will contribute to the efficient development of skills and abilities and the strengthening of student learning.